Strategi Pengembangan Daya Tarik Wisata Pantai Tanjung Bayang Berbasis Prinsip (Attraction, Accesability, Amenities, Ancillary) Pariwisata - Sahra Ainun Abidin; Mukti Ali; Sri Aliah Ekawati (Jurnal Wilayah & Kota Maritim (Journal of Regional and Maritime City Studies), 2019)
Guided by the Regional Spatial Plan (RTRW) of Makassar City, Tanjung Bayang Beach is included in the Development Area of Service City Center (PPK) category IV. PPK IV is a center of a global business activity either internationally, nationally, or regionally as well as considered as a center for meetings, exhibitions, social culture, trade and service activities, tourism, research and higher education institutions, culture, and a sports service center. However, the condition of Tanjung Bayang Beach has not been able to deal with the challenges of the future. This study aims to determine the attraction strategy development of Tanjung Bayang beach based on the principle of 4A Tourism (Attraction, Accessibility, Amenities, Ancillary). This research is considered as a descriptive, qualitative and quantitative with data collection techniques through direct observation, questionnaires, documentation, literature studies using primary and secondary data. The analysis techniques used are descriptive analysis to describe the condition of the existing facilities and infrastructure of Tanjung Bayang’s coastal area, SWOT analysis to obtain a development strategy based on the results of IFAS, EFAS and Cartesian Quadrant and AHP Analysis to obtain a hierarchy of the development priorities. The results of this study, there are 8 (eight) top weight values which are the main development directions based on an average weighting.